Political Legal Studies Related to Medical Professional Education in Indonesia - Novianti Novianti; Clarita Ayu Putri S; Taufiqurrohman Syahuri (Publikasi Indonesia, 2024)
The purpose of this study is to analyze legal politics related to Medical Professional Education in Indonesia which has one important and strategic aspect, namely in relation to the existence of doctors / dentists as a pillar in realizing national health as one of the requirements or indicators in realizing people's welfare as mandated in the Preamble of the 1945 Constitution, which is also a national goal. Its implementation is driven according to the provisions of the applicable laws and regulations in Law No. 17 of 2023 concerning Health, as well as Law No. 20 of 2013 concerning Medical Education. The method used is Normative Juridic. As part of the health service system, the quality of doctors / dentists as health workers is very strategic in health services. In this study, further research will be examined Legal Politics related to Medical Professional Education which is still experiencing obstacles in terms of the length of education travel time and there has not been an even distribution of medical personnel to various regions in Indonesia.